ANALISIS YURIDIS PASAL 30 PERATURAN DAERAH JAKARTA TENTANG VAKSINASI DITINJAU DARI UNDANG-UNDANG HAK ASASI MANUSIA: ANALISIS YURIDIS PASAL 30 PERATURAN DAERAH JAKARTA TENTANG VAKSINASI DITINJAU DARI UNDANG-UNDANG HAK ASASI MANUSIA - Kuswanto, Heru; Retno, Evi (Faculty of Law, University of Dr. Soetomo, 2021)
Human rights are rights inherent in the nature and existence of humans. Even so, human rights violations still occur frequently. This is reflected in the policy issued by the Jakarta Regional Government, namely the Jakarta Regional Regulation Number 2 of 2020 concerning the prevention of Covid-19 article 30 which reads